Estimation of the P Fertilizer Demand of China Using the LePA Model - Yu, Wenjia; Li, Haigang; Nkebiwe, Peteh Mehdi; Li, Guohua; Müller, Torsten; Zhang, Junling; Shen, Jianbo (Frontiers in Environmental Science, 2021)
Modern phosphate (P) fertilizers are sourced from P rock reserves, a finite and dwindling resource. Globally, China is the largest producer and consumer of P fertilizer, and will deplete its domestic reserves within 80 years. It is necessary to avoid excess P input in agriculture through estimating P demand. We used the legacy P assessment model (LePA) to estimate P demand based on soil P management at county, regional and country scales according to six P application rate scenarios: rate in 2012 maintained (1); current rate maintained in low-P counties and P input stopped in high-P counties until critical Olsen-P level (CP) is reached, after which rate equals P-removal (2); rate decreased to 1 – 1.5 kg ha-1 yr-1 in low-P counties after CP is reached and in high-P counties (3); rate in each county decreased to 1 – 8 kg ha-1 yr-1 after soil Olsen-P reached CP in low P counties (4); rate in each county was kept at P-removal rate after reduction (5); P input was kept at the rate lower than P-offtake rate after reduction (6). The results showed that the total P fertilizer demand of China was 750 MT P2O5, 54% of P fertilizer can be saved from 2013 – 2080 in China, and soil Olsen-P of all counties can satisfy the demand for high crop yields. The greatest potential to decrease P input was in Yangtze Plain and South China, which reached 60%. Our results provide a firm basis to analyze depletion of P reserves in other countries.